If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5 + 1) = 12 Combine like terms: 5 + 1 = 6 2(6) = 12 Multiply 2 * 6 12 = 12 Add '-12' to each side of the equation. 12 + -12 = 12 + -12 Combine like terms: 12 + -12 = 0 0 = 12 + -12 Combine like terms: 12 + -12 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 4+11t-1=9t+24-5t | | 3/4(-4-4x)=-3+3x | | -4/7*2/9= | | -5+6(x-3)=15x+5-9x | | 3/4(-4+4x)=-3+3x | | 3/4(4-4x)=-3+3x | | 5(x+4)=(2x-5) | | 3/5-7/10= | | -44=4+6u | | A(5a+c)-2a(c-4a)= | | 4x+y+2=43 | | 3/4(-x+4)=-3+3x | | 10-8/9x=-9 | | 3/10+[-1/5]= | | 2t^2-7t+5=0 | | 3/4(x-4)=-3+3x | | 10y-15=25 | | 3/4(x+4)=-3+3x | | 2*18(x+3)=34 | | 3x-6x+5-7x+8= | | Cw+w-cm-m=0 | | r-43=-33 | | v^2-15v+54=0 | | -2p+5p-9=3(p-4)-5 | | (3z+1)(4z+1)(6z+1)(12z+1)=2 | | 7x-4=3x+1+9x-5 | | -4-7x=2x+15 | | 4r-9=55 | | 4x+14(-14)-3+(-14)= | | 16+8x=24+6x | | -4(-x+4)=-4x+16 | | 16-4x= |